2015
DOI: 10.1161/hypertensionaha.114.04576
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory Cerebral Blood Flow Is Associated With Impaired Neurocognition and Functional Hyperemia in Postural Tachycardia Syndrome During Graded Tilt

Abstract: We hypothesize upright cognitive impairment in Postural Tachycardia Syndrome is due to reduced cerebral blood flow. Cerebral blood flow velocity measured by transcranial Doppler ultrasound decreased excessively during 70° tilt in a minority of patients with intermittent hyperpnea/hypocapnia. Incremental tilt showed no difference in mean cerebral blood flow velocity. But, N-Back memory tasking indicated progressive compromised memory, reduced functional hyperemia and reduced neurovascular coupling. Orthostasis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 40 publications
5
32
0
Order By: Relevance
“…However, studies using transcranial Doppler ultrasonography showed that patients with POTS and healthy controls have near identical blood flow velocities in the middle cerebral artery, which decreased equally with increasing levels of tilt [ 36 , 37 ]. Instead, POTS patients showed an increase in low-frequency oscillatory blood flow with increasing levels of tilt, whereas controls did not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies using transcranial Doppler ultrasonography showed that patients with POTS and healthy controls have near identical blood flow velocities in the middle cerebral artery, which decreased equally with increasing levels of tilt [ 36 , 37 ]. Instead, POTS patients showed an increase in low-frequency oscillatory blood flow with increasing levels of tilt, whereas controls did not.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, POTS patients showed an increase in low-frequency oscillatory blood flow with increasing levels of tilt, whereas controls did not. The authors argued that these increased low-frequency oscillations are an expression of impaired cerebral autoregulation and that they might interfere with normal neurovascular coupling [ 37 ]. Low ICC in our high-OI patients may have put a limit on their ability for dynamic cerebral autoregulation, thereby resulting in similar low-frequency blood flow oscillations.…”
Section: Discussionmentioning
confidence: 99%
“…Further study attributed loss of NVC in POTS to oscillatory cerebral blood flow rather than a decrease in mean CBF (Stewart et al. , ). Disruption of NVC has been shown in diabetes, depression, hypertension, stroke, and Alzheimer's disease.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive difficulty, often described as “brain fog”, is a prevalent complaint among patients with POTS 6 . Interestingly, brain fog has been reported to occur even in the supine position and may not be limited to upright posture 7 . Others have demonstrated an approximately 25% increase in cerebral blood flow (CBF) velocity in the posterior cerebral artery (PCA) of healthy individuals in response to visual stimuli 8 .…”
Section: Introductionmentioning
confidence: 99%